Predictor-Based CACC Design for Heterogeneous Vehicles With Distinct Input Delays - Amirhossein Samii; Nikolaos Bekiaris-Liberis (IEEE Open Journal of Intelligent Transportation Systems)
We develop a predictor-based cooperative adaptive cruise control (CACC) design for platoons with heterogeneous vehicles, whose dynamics are described by a third-order linear system subject to actuators delays, which are distinct for each individual vehicle. The design achieves individual vehicle stability, string stability, and zero, steady-state speed/spacing tracking errors, relying on a nominal, constant time headway (CTH)-type CACC design that achieves these specifications when all actuators’ delays are zero. This is achieved owing to the delay-compensating mechanism, of the CACC law introduced, for long delays and despite the fact that each vehicle’s dynamics are subject to different input delays, which makes the available predictor-feedback CACC designs inapplicable. The proofs of individual vehicle stability, string stability, and regulation rely on employment of an input-output approach on the frequency domain. We present consistent simulation results, including an example in which we employ real traffic data for the trajectory of the leading vehicle and an example via which we compare the performance of our design with the existing, predictor-feedback CACC and predictor-based ACC laws. In addition, we study numerically the robustness properties with respect to string stability of our predictor-based CACC design to (uncertain) communication delays. Thus, our numerical results validate the performance of the design in realistic scenarios and as compared with related, existing control laws.